2020
DOI: 10.1186/s12910-020-00546-7
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between the perception of open disclosure of patient safety incidents, perception of patient safety culture, and ethical awareness in nurses

Abstract: Background Scientific advances have resulted in more complex medical systems, which in turn have led to an increase in the number of patient safety incidents (PSIs). In this environment, the importance of honest disclosure of PSIs is rising, which highlight the need to settle a reliable system. This study aimed to investigate the effects of patient safety culture and ethical awareness on open disclosure of PSIs. Methods Data were collected from 389 nurses using self-reported perceptions of open disclosure of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
1
2

Year Published

2022
2022
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 25 publications
0
13
1
2
Order By: Relevance
“…In Korea, previous research has reported on patient safety including the operating room environment and communication procedures; 9 , 10 and an analysis of the perception of patient safety and related factors has been undertaken. 11 However, these previous studies have focused on nurses more than physicians.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In Korea, previous research has reported on patient safety including the operating room environment and communication procedures; 9 , 10 and an analysis of the perception of patient safety and related factors has been undertaken. 11 However, these previous studies have focused on nurses more than physicians.…”
Section: Introductionmentioning
confidence: 99%
“…11 However, these previous studies have focused on nurses more than physicians. 9 – 11 In contrast, studies on the effects of patient safety attitude of surgical teams, including physicians, on the surgical time-out are difficult to find. Therefore, the objectives of this study were: (i) to compare the differences in perception of patient safety attitude, surgical time-out and recognition count error between nurses and doctors; and (ii) to identify correlations between perceived safety attitude, surgical time-out and recognition count error.…”
Section: Introductionmentioning
confidence: 99%
“…Given that HVNs provide care at the patient’s home, any potential mistakes are difficult for others to detect. Education on basic ethical values is important to raise nurses’ awareness of public disclosure of malpractice by patients [ 40 ]. Nurses’ ethics influence their perceptions and behavior toward patient safety.…”
Section: Discussionmentioning
confidence: 99%
“…Iniciativas internacionais têm desenvolvido normas de disclosure como tentativa de solução para melhoria dos cuidados em saúde (4) (5) (7) Com raras exceções, infelizmente, as instituições de saúde e as universidades no Brasil não preparam seus profissionais para informar adequadamente o paciente e seus familiares a ocorrência de danos (8). Como consequência, a falha na comunicação reduz a confiança entre pacientes e profissionais e aumenta a possibilidade de ocorrência de processos judiciais.…”
Section: Desafios Para a Implementação Do Disclosureunclassified
“…Já há evidências que comunicar ao paciente um dano cometido durante os cuidados, tem vantagens econômicas e jurídicas, sendo uma iniciativa apoiada por profissionais, pacientes e familiares em muitas organizações internacionais de saúde (6). Para que a divulgação acerca de algum dano seja eficaz, os profissionais devem sempre comunicar-se com o paciente de maneira transparente (7). E para que a prática do disclosure alcance sua finalidade, a ação deve ser sempre acompanhada pelo pedido de desculpas.…”
Section: Introductionunclassified